Village-owned enterprises: analysis and modeling (Study on 69 Villages-Owned Enterprises in Belu District - NTT Province) - Noldy D. P Mumu; Patrisius Seran (Institute of Computer Science (IOCS), 2023)
The purpose of this study is to explore and map in depth about BUM Desa starting from the institutional, organ and governance system, stakeholders to various problems faced, then analyze it for further designing and recommending a comprehensive and comprehensive Re-Modeling. strategic as a solution for the management of BUM Desa in Belu Regency in particular and in East Nusa Tenggara Province in general. The method used in this study is descriptive qualitative because this method is considered to be able to provide a broader, in-depth and detailed description of the phenomena in the field, in this case the reality conditions of BUM Desa in Belu district. The results of the study show that the problems that have hindered all BUM Desa in Belu district have so far stemmed from the absence of a standardized formal model starting from pre-operational; operational implementation; post operational.